MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA KELAS IX-A SMP NEGERI 3 PARINGIN DENGAN MENGGUNAKAN MEDIA DALAM PEMBELAJARAN KOOPERATIF TIPE JIGSAW PADA MATERI BANGUN RUANG SISI LENGKUNG - Meina Noriyana (Universitas Lambung Mangkurat, 2014)
Abstract. This study aims to improve the activity and results of students of class IX-A SMPN 3 Paringin, materials with curved side to use the media in cooperative learning of Jigsaw. The research method used was classroom action research that consists of four phases: planning, action, observation, and reflection. The subjects were students of class IX-A SMPN 3 Paringin the academic year 2013/2014, totaling 17 people. Data collected through observation sheet to determine the learning activities in class and test instruments to determine the level of understanding / student learning outcomes. This study was conducted in two cycles and at every meeting ends with the execution of tests that can be known whether there is an increase in activity and student learning outcomes with curved side material in math. Research says that the jigsaw cooperative learning model can (1) increase the activity of students with active category, (2) Improve student learning outcomes from cycle 1 to cycle 2 with individual completeness of 7 students to 15 students. Based on these results indicate that by using the media in cooperative learning jigsaw can enhance the activity adan learning outcomes of students of class IX-A SMPN 3 Paringin so it can be used as an alternative model of learning mathematics and can be recommended to teachers to implement cooperative learning jigsaw for can enhance students' understanding of mathematics.Keywords: Jigsaw, activity and learning outcomes